Metal Organic Frameworks Modified Proton Exchange Membranes for Fuel Cells - Liu, Quanyi; Li, Zekun; Wang, Donghui; Li, Zhifa; Peng, Xiaoliang; Liu, Chuanbang; Zheng, Penglun (Frontiers in Chemistry, 2020)
Proton exchange membrane fuel cells (PEMFCs) have received considerable interest due to their low operating temperature and high energy conversion rate. However, their practical implement suffers from significant performance challenge. In particular, proton exchange membrane (PEM) as the core component of PEMFCs, have shown a strong correlation between its properties (e.g., proton conductivity, dimensional stability) and the performance of fuel cells. Metal-organic frameworks (MOFs) as porous inorganic-organic hybrid materials have attracted extensive attention in gas storage, gas separation and reaction catalysis. Recently, the MOFs-modified PEMs have shown outstanding performance, which have great merit in commercial application. This manuscript presents an overview of the recent progress in the modification of PEMs with MOFs, with a special focus on the modification mechanism of MOFs on the properties of composite membranes. The characteristics of different types of MOFs in modified application were summarized.